Palaeomagnetic assessment of tectonic rotation in Northeast Asia：implications for the coupling of intracontinental deformation and mantle convection. Issue 17 (21st November 2020) - Zhou, Zaizheng; Li, Sanzhong; Guo, Lingli; Li, Xiyao; Jiang, Zhaoxia; Liu, Yongjiang; Li, Yang; Wang, Guangzeng; Lan, Haoyuan; Guo, Runhua; Wang, Yini; Somerville, Ian
ABSTRACT: Knowledge of the displacement history of the series of continental fragments in Northeast Asia is key to understanding the plate kinematic evolution of the western peri-Pacific tectonic domain. Palaeomagnetism is an effective approach for deciphering the horizontal movements of crustal elements, especially vertical-axis rotations. Here we present a set of new palaeomagnetic data from Lower Cretaceous volcanic rocks from the northeastern part of the North China Block (NCB), and from Lower Cretaceous sedimentary and volcaniclastic rocks from the Bureya-Jiamusi-Khanka terrane. The data suggest that the northeastern NCB crustal elements underwent a clockwise motion relative to the Eurasian continent after the Early Cretaceous, and in addition a substantial counterclockwise deformation component is observed in the Bureya-Jiamusi-Khanka terrane. Combined with the results of previous Cretaceous and Cenozoic palaeomagnetic studies, we suggest that the northeast part of the North China Block and the Korean Peninsula experienced ~20° of clockwise rotation during the Cenozoic. However, the Bureya-Jiamusi-Khanka terrane and its eastern neighbouring Pacific-related accretionary terranes, such as the Sikhote-Alin Orogenic belt, however, underwent a contemporaneous 40°counter-clockwise rotation. The Japanese Islands, with juvenile crust in the easternmost part of Asia, were divided into a pair of terranes, which rotated in opposite directions during the Middle Miocene. The opposing senses of rotation are attributed to mantle wedge convection. We suggest that tectonic rotations of parts of Northeast Asia are controlled by the subduction of the western Pacific Plate via lithospheric deep-shallow coupling. The two critical events were coeval with ridge subduction of the Izanagi-Pacific mid-ocean ridge under the continental margin during the Palaeocene, and the collision of the Izu-Bonin and Japanese Islands during the Middle Miocene, respectively.